İşgücü Verimliliği Karşısında Parkinson Kanunu - Meçik, Oytun (İstanbul Kültür Üniversitesi / İktisadi ve İdari Bilimler Fakültesi / İktisat Bölümü, 2016)
Labor productivity is a measure of how much value a business can create with its workforce. Labor productivity can be increased by increasing the flexibility, interchangeability and mobility of various parts of the labour force – but these all involve the need for efficient organizational change. Obviously, productivity is not determined solely by how hard and how well people work. There are technical factors such as technological development, the quality of raw materials, the layout of the work, and methods and techniques. Thus, the systems, formality, and controls of the bureaucracy is getting to be a crucial issue to solve productivity problems versus Parkinson’s Law which can be summarized as “work expands so as to fill the time available for its completion”.
Keywords: Parkinson Kanunu; İşgücü Verimliliği; İstihdam; Parkinson’s Law; Labor Productivity; Employment